(untitled) (Journal of Oriental Studies, 2016)
In this article the urgency of using сompetenсе- oriented technology used in teaching the discipline "Intercultural communication and translation problems." The author presents his own method of teaching this distsiliny and makes recommendations for successful implementation сompetenсе- oriented technology in the educational process.